USE OF MAGNETOTELLURIC SOUNDING DATA TO ELUCIDATE THE CONVECTIVE STRUCTURE OF THE MANTLE - Bulashevich Y.P.; Khachay Y.V.; Khachay O.A. (My University, 1989)
Analysis of available geological and geophysical data indicates that slow convective flows occur in certain regions in the mantle. Many investigators have studied the structure of such flows, but the measurements cannot be used to determine whether the convection is confined to the upper mantle, or whether it involves the entire thickness of the mantle. It is therefore of interest to find measurable phenomena that can assist in the solution of this problem. We shall use the equation relating the electrical conductivity of the mantle to its temperature and pressure, derived by Zharkov and Trubitsyn, to extract certain features from magnetotelluric sounding data obtained above regions with different types of convective flows. The results indicate that magnetotelluric sounding data may contain information on the presence and structure of present-day convection in the mantle. Complete plots of ρ a and φ must be recorded for this purpose, and particular attention must be devoted to periods between 4·10 2 and 30·10 4 sec. Comparison of soundings in ocean and continental areas indicates that it is possible to evaluate the relative rate of mantle convection.